Dependencies of the lead of front driving wheels on different tire deformations for a MFWD tractor - Janulevičius, Algirdas; Pupinis, Gediminas; Lukštas, Justas; Damanauskas, Vidas; Kurkauskas, Vaclovas (Transport, 2017)
Tractors are the main machines in agricultural production processes. Agricultural tractors commonly employ a four-wheel drive transmission. To reach maximum efficiency in production works, tractors are loaded by as high thrust as possible. The consequence of it, quite often, is that the slippage of driving wheels grows to the limit that is not allowed. To reduce the slippage, various ways are pointed out in terramechanics. One way is to increase the tractor’s weight by adding ballast. The other way is to increase the contact area between tires and the supporting surface. The slippage can be also reduced with traction control and other relevant systems. These methods, which help to reduce slippage, also affect tire deformation. When proportion of tires deformation is not the same as proportion of their sizes, the consequence is change of the lead of front wheels. In this paper analysis is presented, how the lead of front wheels affects the work of MFWD tractor in different conditions. Test results are presented for a MFWD tractor, how the lead of front wheels varies depending on deformation ratios between front and rear tires. For a MFWD tractor, values of deformation ratio between front and rear tires were determined, which ensured effective and which produced unreasonable values of lead of front wheels.First published online: 17 Jul 2015